New supermarket for Jurong West - Mohammed Effendi Basri (2015)
The purpose of this report is to determine the need, attractiveness and viability of opening a new supermarket in Jurong West, a developing estate. This topic is selected because of an observed lack of supermarket in Jurong West. Both primary and secondary data were used. The primary research includes interviews, mailed questionnaire, and observation. The sources of secondary data include literature, statistical report, companies financial reports and periodicals. The need for a new supermarket was determined using the Saturation Theory, and through the assessment of the various population and household characteristics of Jurong West. In addition, an analysis was done on the major potential competitors of the new supermarket. The analysis concludes that a need for the new supermarket exists. With a market to tap, the marketing strategies for the achievement of the expected sales level were outlined. Two operating years' projected financial statements were also drawn to show the feasibility and viability of the project. In the projected income and expenditure statements, the Turnover was estimated using a pro forma strategic model. The operating expenses were derived by prorating the specific industrial cost items, either in terms of the floor area of the new supermarket or the industry percentage of Turnover. In conclusion, the group believes that the supermarket will be able to achieve stable growth and profits in approximately two to three years' time. This is based on the favourable projected financial statements, and other qualitative factors, such as a growing population, and an unsatistied need.